Georiddles, brainstorming and creativity in natural and cultural tourism - Rosendahl, Stefan (2022)
Many tourists don’t want to spend their holidays only at the beach and others arrive to their destination for cultural or natural reasons. Some are attracted by creative activities. An upcoming touristic branch which joins cultural and natural tourism is Geotourism. A “georiddle” may increase the visitor’s interest in geological and cultural themes and challenge his creativity. The following methodology is adopted to reach these objectives: The guide gives basic information in a geologically interesting site and asks the participants about details of what can be seen. By brainstorming and discussion, they may solve the problem or not; in any case the participants are encouraged to foster their creativity by interactive processes. Then, the guide explains his opinion about the solution of the “georiddle”, and the discussion can begin again. Enigmatic structures may be found in construction stones of built heritage, as well as in geological outcrops in the countryside. A “georiddle” can be posed in other fields, like vernacular cultural heritage. For instance, drystone constructions are interfaces between geological and cultural heritage. Here, the riddle’s aim may be to discuss about the reason of their spatial arrangement and purpose. As a result, it is expected to awaken the visitor’s curiosity and creativity and to increase and broaden his field of knowledge.